An (Distinctive) Example of Strengtening a Validity: Self-evaluation of the School Based Action Research - Yıldız Uzuner (Anı Publishing, 2018)
It is important to evaluate any research effort in order to see if it is scientifically based research. It is much easier to analyze someone else's work. As action researchers, the researchers are insiders of their research efforts. On the other hand, self-evaluation of one's own research effort would strengthen the research process and provide strong basis for the future research efforts. The author has focused on the self-evaluation of the action research directed by herself. Utilizing the evaluation schema offered by Malone (2014) she aims to prompt enhanced understanding about the evaluation of action research project. In conclusion, it could be approved that the schema offered by Malone is comprehensive and valid tool for evaluation action research projects. In the light of this schema the analyzed action research project is considered as scientifically based research. The author recommends the other researchers utilize this schema to evaluate their action research project.